2016
DOI: 10.1145/2914796
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interpersonal Attitude of a Group of Agents on User’s Presence and Proxemics Behavior

Abstract: In the everyday world people form small conversing groups where social interaction takes place, and much of the social behavior takes place through managing interpersonal space (i.e., proxemics) and group formation, signaling their attentio to others (i.e., through gaze behavior), and expressing certain attitudes, for example, friendliness, by smiling, getting close through increased engagement and intimacy, and welcoming newcomers. Many real-time interactive systems feature virtual anthropomorphic characters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Furthermore, an adequate welcome for new group members is required, e.g., a head node [11], mutual gaze, smiling, and adapted proxemics [10]. Especially if users are supposed to interact more often with the group members, a friendly and open group is preferred [9] as users feel more included [10]. Volonte et al furthermore found that VAs with a positive attitude can be used to foster simulated social dialogues as users are more encouraged to engage in a social interaction [39].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, an adequate welcome for new group members is required, e.g., a head node [11], mutual gaze, smiling, and adapted proxemics [10]. Especially if users are supposed to interact more often with the group members, a friendly and open group is preferred [9] as users feel more included [10]. Volonte et al furthermore found that VAs with a positive attitude can be used to foster simulated social dialogues as users are more encouraged to engage in a social interaction [39].…”
Section: Related Workmentioning
confidence: 99%
“…Volonte et al furthermore found that VAs with a positive attitude can be used to foster simulated social dialogues as users are more encouraged to engage in a social interaction [39]. Based on Cafaro et al, the out-group behavior, defined as the non-verbal behavior towards the user as an outstander who is about to join the group, has a great influence and should be modeled with care [9].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Social behaviors and norms, such as politeness, and interpersonal attitudes such as friendliness, have been studied in previous research works involving virtual agents. Cafaro et al [4] studied the effect of in-group and out-group friendliness of a group of agents on user's presence and proxemics behavior while joining or passing a group. Linssen et al [13] investigated how stances corresponds to certain politeness strategies.…”
Section: Politeness and Interpersonal Attitude In Artificial Systemsmentioning
confidence: 99%